OP0224 Similar short term clinical response to initial treatment with high versus low dose methotrexate in mono- and combination therapy in early rheumatoid arthritis patients. (15th June 2017) - Bergstra, SA; Allaart, CF; Berg, R van den; Chopra, A; Govind, N; Huizinga, TW; Landewé, RB; ,
Abstract : Background: Aiming at rapid decrease of disease activity, there has been a trend to start with higher doses of methotrexate (MTX) in newly diagnosed rheumatoid arthritis (RA) patients, both as monotherapy and in combination with other antirheumatic drugs (DMARDs). We hypothesized that in combination with other very effective medication, there might be no additional benefit of high over low doses of MTX. Objectives: To compare early clinical response to high versus low doses of MTX in mono- and combination therapy in DMARD naive early RA patients. Methods: RA patients included in the observational international METEOR cohort with symptom duration ≤5 years, time between diagnosis and first visit ≤2 months, MTX prescribed as (part of) first treatment, no medication change within 3 to 6 months after treatment start and available outcome data on disease activity, were selected. Patients were divided into 4 medication groups: MTX monotherapy, MTX + synthetic (cs)DMARDs, MTX + oral glucocorticoid (+ possibly csDMARDs) or MTX + biologic (b)DMARDs (+ possibly csDMARDs). Missing data were imputed using multivariate normal imputation. MTX dose was dichotomized: low dose ≤10 mg/week; high dose ≥15 mg/week. A propensity score (PS) was calculated to adjust the relationship between MTX dose and outcome for potential confounding by indication. Linear mixed model analyses for DAS, DAS28, and HAQ were performed for each medication group, with MTX-dose and time (days between assessment visit and baseline assessment) as co-variates. Associations were adjusted for the PS. Random intercept and slope were used to account for irregular time intervals between visits. Results: Patients who started on MTX monotherapy had lower baseline disease activity and fewer were erosive and autoantibody positive; other baseline characteristics were comparable between medication groups. The number of patients on combination therapy with bDMARDs was too small to perform analyses (26 visits in 11 patients). For patients starting on MTX monotherapy, MTX+csDMARDs or MTX+glucocorticoids, the PS-adjusted effects of MTX-dose (high vs low) on DAS, DAS28 and HAQ were small and not clinically meaningful. The unadjusted main associations between MTX-dose and outcomes were often in opposite direction and/or much larger than the PS adjusted associations, suggesting that confounding by indication indeed plays a role and that (at least some) correction was achieved by adjusting for the PS (table 1 ). Conclusions: In a daily practice derived database in DMARD-naive early RA patients, we found no early clinical benefit of high over low initial MTX doses, neither for MTX monotherapy nor for combination therapy with MTX and csDMARDs or glucocorticoids. This seems to contradict a general trend over time to start higher MTX-doses. Disclosure of Interest: None declared